2007
DOI: 10.1007/s10549-007-9556-1
|View full text |Cite
|
Sign up to set email alerts
|

An overview of prognostic factors for long-term survivors of breast cancer

Abstract: Background Numerous studies have examined prognostic factors for survival of breast cancer patients, but relatively few have dealt specifically with 10+-year survivors. Methods A review of the PubMed database from 1995 to 2006 was undertaken with the following inclusion criteria: median/mean follow-up time at least 10 years; overall survival and/or disease-specific survival known; and relative risk and statistical probability values reported. In addition, we used data from the long-standing Eindhoven Cancer Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
301
5
25

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(351 citation statements)
references
References 115 publications
20
301
5
25
Order By: Relevance
“…Interestingly, tumors obtained from mice immunized with pcDNA3.1-transfected cancer cells had higher histological grades and tumor sizes than those from mice immunized with Stat3Y705F-transfected cancer cells. A 10-y follow-up of breast cancer patients showed that tumor size, nodal status, and tumor grade remained the most important prognostic factors for long-term survival (38) and were also predictors for distant metastasis (39). Importantly, we found that immunization with Stat3-inhibited breast cancer cells decreased tumor grade, tumor growth, and metastasis, the most important prognostic indicators in breast cancer.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, tumors obtained from mice immunized with pcDNA3.1-transfected cancer cells had higher histological grades and tumor sizes than those from mice immunized with Stat3Y705F-transfected cancer cells. A 10-y follow-up of breast cancer patients showed that tumor size, nodal status, and tumor grade remained the most important prognostic factors for long-term survival (38) and were also predictors for distant metastasis (39). Importantly, we found that immunization with Stat3-inhibited breast cancer cells decreased tumor grade, tumor growth, and metastasis, the most important prognostic indicators in breast cancer.…”
Section: Discussionmentioning
confidence: 59%
“…(34,35) Tumor size, node status, historical grade, hormone receptors (HR), and Her-2 ⁄ neu status have been used with limited success as the biomarkers. (36)(37)(38)(39) Currently, breast cancer is commonly subclassified on the basis of the presence of ER, PR, and the HER-2 ⁄ neu status. Breast cancers can be divided into HR + ⁄ HER-2 ) , HR + ⁄ HER-2 + , HR ) ⁄ HER-2 + , and HR ) ⁄ HER-2 ) (triple-negative).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Early diagnosis associated with treatment could reduce the mortality of the disease. [8][9][10][11][12] Disease-free survival (DFS) is defined as the time between the beginning of the treatment and disease progression or death from any cause. [13][14][15] Factors related to a shorter DFS include tumors larger than 2 cm, the presence of lymph node involvement and more advanced stages of the disease.…”
Section: Introductionmentioning
confidence: 99%